Flint Hills Inspiration (Symphony in the Flint Hills, 2009)
Selected Kansas artists who paint in the Flint Hills have been invited to submit original artwork to Symphony in the Flint Hills. Thirteen artists have entries for judging this year. One work has been selected for this year's limited edition print. All entries will be auctioned at the Symphony on concert day. In this Journal artists participating in this year's Symphony are listed.
Keywords: Artists; art; life; love; career; Pastel Society; painter; Galleries; Flint Hills